ARTIFICIAL INTELLIGENCE AND LOAN RISK MANAGEMENT IN ALGERIAN PUBLIC BANKS: A FORWARD-LOOKING STUDY OF THE POSSIBILITY OF ADOPTION AND PROSPECTS FOR APPLICATION - Ouided, Boufafa (The journal of contemporary issues in business and government, 2024)
This research paper aims to examine the prospects for the adoption of artificial intelligence technology for effective loan risk management at the level of the Algerian banking system. In the context of efforts to keep pace with the global digital trend, the Algerian authorities have made profound reforms to this important economic agent. Additionally, via a scoping research that uses a descriptive methodology and is backed by a case study. Academic researchers, officials inside the framework, and representatives of loan-seeking firms at the level of Algerian state banks were the three categories of players targeted in the lending process. Depending on the interview. The study discovered that the sample dialects supported the digital track and experiment, notwithstanding differences in opinion between advocates and opponents of its usage. Uncertainty surrounds the perception of artificial intelligence as a cutting-edge financial technology that competes with conventional banking services.